Age effects on the climatic signal in Araucaria araucana from xeric sites in Patagonia, Argentina - Hadad, Martín Ariel (2014)
Background: At different cambial ages, trees experience changes in their structure and interactions with environmental conditions. Reciprocal mechanisms between tree age and physical resources, photosynthetic rates, and xylem production may influence hydraulic resistance and plant water stress. However, it is yet uncertain how these mechanisms are associated with changes in growth sensitivity to biophysical drivers, especially climate. Aim: To establish age-associated climate - growth relationships in growth rings of Araucaria araucana trees from the temperate xeric zones of northern Patagonia, Argentina. Methods: We analysed the growth in 211 A. araucana trees from four sampling sites, in three age classes: young (≤120 years), mature (121-275 years), and old (≥276 years). We explored the correlations between the signal strength of tree growth and climate, based on comparisons between each age-class chronology and monthly mean surface air temperature, total precipitation, and the Southern Annular Mode (SAM) index. Results: The young trees showed higher correlations when their growth was compared with precipitation, air temperature, and the SAM index during austral spring and summer months of the same year. In contrast, growth in mature and old trees showed higher correlations with summer temperatures of the previous growing season. Conclusions: The sensitivity of the radial-growth response of A. araucana to climate varies with age and is strongest in the rings of young trees.